Principles of building and analyzing public key infrastructures based on the use of blockchain technology - Горбенко, І.Д.; Потій, О.В.; Горбенко, Ю.І.; Пушкарьов, А.І.; Єсіна, М.В. (Radiotekhnika, 2019)
The paper provides a rationale for the possibilities and the need to create blockchain-based public key infrastructure. An improved public key infrastructure model with blockchain-based certificate transparency as well as the main problematic issues of promising blockchain-based public key infrastructures are analyzed. A general assessment of the public key infrastructure based on the blockchain stability in conditions of well-known attacks is carried out.